Dietary attitude of adults with type 2 diabetes mellitus in the Kingdom of Saudi Arabia: A cross-sectional study - Sami, Waqas; Alabdulwahhab, Khalid M.; Ab Hamid, Mohd Rashid; Alasbali, Tariq A.; Al Alwadani, Fahd; Mohammad Shakil, Ahmad (MDPI AG, 2020)
Background and objectives: There is a paucity of literature on the dietary attitude (DA) of patients with type 2 diabetes in the Kingdom of Saudi Arabia (KSA). Although the prevalence of diabetes mellitus (DM) is high in Gulf countries, there remains a lack of understanding of the importance of dietary behavior in diabetes management among patients. Understanding the behavior of patients with diabetes towards the disease requires knowledge of their DA. Therefore, this study aimed to assess and evaluate the DA of type 2 diabetes patients, and it is the first of its kind in the KSA. Material and Methods: An analytical cross-sectional study was conducted among 350 patients with type 2 diabetes. A self-administered DA questionnaire was used to collect the data. Psychometric properties of the questionnaire were assessed by face validity, content validity, exploratory factor analysis, and internal consistency reliability. The data were collected using a systematic random sampling technique. Results: The overall DA of the patients was inappropriate (p = 0.014). Patients had an inappropriate DA towards food selection (p = 0.003), healthy choices (p = 0.005), food restraint (p < 0.001), health impact (p < 0.001), and food categorization (p = 0.033). A poor DA was also observed in relation to the consumption of red meat (p <0.001), rice (p < 0.001), soup and sauces (p = 0.040), dairy products (p = 0.015), and junk food (p < 0.001). Conclusions: It is highly recommended that patients with diabetes receive counseling with an empowerment approach, as this can bring about changes in their dietary behavior, which is deeply rooted in their daily routine. Healthcare providers should also be well-informed about patients’ attitudes and beliefs towards diabetes to design tailored educational and salutary programs for this specific community. Diabetes self-management educational programs should also be provided on a regular basis with a special emphasis on diet and its related components.